Benign duodenocolic fistula: A case report and review of the literature - Li, Zeyu; Peng, Wenjing; Yao, Hongliang (Frontiers in Surgery, 2023)
Duodenocolic fistula is a rare upper gastrointestinal fistula, divided into benign duodenocolonic fistula and malignant duodenocolic fistula. Duodenocolic fistulae are often the complications of advanced colon cancer. However, benign duodenocolic fistula is rarer. The most common cause of benign fistula is a perforated duodenal ulcer. We report a case of benign duodenocolic fistula. The patient presented with abdominal pain, diarrhea, and weight loss. Gastroscopy and upper gastrointestinal study confirmed the presence of fistula. Surgery was performed. Pathologic examination demonstrated that the fistula originated from the duodenal ulcer.